2016
DOI: 10.1002/app.43885
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin electrospun PANI nanofibers for neuronal tissue engineering

Abstract: N-(4-aminophenyl)aniline oxidative polymerization is optimized to produce polyaniline (PANI) free from carcinogenic and/or polluting coproducts. The resulting polymer is electrospun using polymethyl methacrylate (PMMA) as the supporting polymer, with different weight ratios (1:0, 4:1, 3:1, 2:1, 1:1, and 0.5:1 w/w PANI/PMMA). By rinsing with a selective solvent, PMMA is removed while maintaining the fibrous morphology. Ultrathin (65 6 14 nm) and defect-free PANI nanofiber mats are obtained for the blend contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…In the literature, electrospun PANI fibers had a wide range of conductivity, depending on many factors, such as the selection of matrix polymer, the volumetric ratio of the matrix polymer to doped PANI, and fiber morphologies. For instance, the conductivity of PANI and PEO blends was in the magnitude of 10 1 S/cm to 10 −4 S/cm in some studies [20,22], and the conductivity of PANI and PVP mats was lower than 10 −8 S/cm reported by others [23,26,29,30,31,33,35,36,37,38,39,40,41,42]. It is also noteworthy that the conductivity testing method is a non-negligible factor.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In the literature, electrospun PANI fibers had a wide range of conductivity, depending on many factors, such as the selection of matrix polymer, the volumetric ratio of the matrix polymer to doped PANI, and fiber morphologies. For instance, the conductivity of PANI and PEO blends was in the magnitude of 10 1 S/cm to 10 −4 S/cm in some studies [20,22], and the conductivity of PANI and PVP mats was lower than 10 −8 S/cm reported by others [23,26,29,30,31,33,35,36,37,38,39,40,41,42]. It is also noteworthy that the conductivity testing method is a non-negligible factor.…”
Section: Resultsmentioning
confidence: 88%
“…Electrospinning was the most common spinning method to prepare PANI fibers due to its versatility for comprehensive purposes and applications. Poly(ethylene oxide) (PEO), poly(lactic acid), polyvinylpyrrolidone, poly(methyl methacrylate), poly(vinylidene fluoride), and polystyrene have been frequently reported for blending with PANI [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]. Among these, PEO is the most used matrix polymer [20,21,22,23,43,44,45,46] because of its good spinnability and availability in wide range of molecular weight along with the nontoxic, fully biodegradable, and biocompatible traits [47].…”
Section: Introductionmentioning
confidence: 99%
“…It should be underlined that the reaction cannot proceed further without the addition of H 2 O 2 , as clearly shown by the change in color from violet to dark green, characteristic of polyaniline, upon H 2 O 2 addition. Oxygen peroxide is known to act as both a radical source initiating PANI synthesis, as well as an oxidant supporting the polymer growth [72]. In PANI_ref synthesis, previous studies have shown that H 2 O 2 dissociation in the presence of a catalyst can produce radical species (HO•) able to promote the formation of initiators (aniline dimer radicals) [72].…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen peroxide is known to act as both a radical source initiating PANI synthesis, as well as an oxidant supporting the polymer growth [72]. In PANI_ref synthesis, previous studies have shown that H 2 O 2 dissociation in the presence of a catalyst can produce radical species (HO•) able to promote the formation of initiators (aniline dimer radicals) [72]. These are crucial for the first part of the reaction, which follows a radical mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, possibilities to sterilize nanofi brous mats before the addition of cells and their potential infl uences on cell growth are only scarcely mentioned in the scientifi c literature. Castagna et al performed autoclaving and UV irradiation to sterilize polyaniline nanofi brous mats [25]. Arnal-Pastor et al used immersion in 70% ethanol for 3 hours, which necessitated careful rinsing with sterile phosphatebuff ered saline to remove ethanol residues, making this method very time-consuming [26].…”
Section: Introductionmentioning
confidence: 99%